Pina Manique: a trajetória do Intendente de Polícia e sua ação junto à saúde pública em Portugal, 1780-1805 - Oliveira, Fabricio Andre de (2022)
This paper aims to follow the trajectory of the Portugal’s General Intendant of Police, Diogo Ignácio de Pina Manique (1780-1805), especially his performance in the political field, trying to reconstruct the networks of social relationships in which he participated and helped to build, as well as his contributions to transform the relationship between secular institutions and the General Intendency of Police of the 18th century. In dealing with the character, an attempt is made to establish dialogues with three main axes: the trajectory itself, the role of the police in Modernity, and the public health issues highlighted in that context. In this way, it is intended to highlight the networks that surrounded the life and performance of Pina Manique, based on the theoretical-methodological assertions of P. Bourdieu (1996) and S. Loriga (2011) on the biographical plot. The historical sources that support this research are diverse; they are laws, decrees, personal letters from the intendant, notarial records, and a whole range of official documents produced during the Marian period (1777-1816). Through a thorough documentary analysis of such sources, this paper seeks to follow the public ascension of Pina Manique to the position of Intendant of Police of the Kingdom in 1780, the main projects undertaken by him, as well as the contexts that marked his successes and failures. Meanwhile, it aims to problematize the insertion of Portugal in the debates on public health that marked the European context, in order to identify the circulation of ideas and knowledge through the actions undertaken by Pina Manique at that conjuncture. Far from considering him a hero or villain, the intention is to observe what the fragments of the past reveal to us, as the trajectories are neither linear nor isolated, being crossed by several others, by a countless number of events. In this sense, this research could help other researchers revisit the history of Diogo Ignácio de Pina Manique, as well as the history of Portugal itself, from other perspectives, contributing to a richer and more multifaceted history.